Peran Citra Merek dan Influencer Endorsement terhadap Minat Beli Produk Whitelab - Jasica Roeytashya; Alnov Martin; Griselda Tjandra (Journal of Economics, Management, and Accounting, 2026)
This study was motivated by the rapid growth of the beauty industry in Indonesia and the increasing competition among local skincare brands, one of which is WhiteLab, which requires a deeper understanding of the psychological and symbolic factors that influence consumer purchasing decisions. The focus of this study is to analyze the influence of brand image and influencer endorsement on the purchasing interest of WhiteLab products in Palembang City, both partially and simultaneously. The research uses a quantitative approach with a descriptive-associative design, involving 112 respondents who have used or are familiar with WhiteLab products, with data collection through questionnaires. Data analysis was performed using validity, reliability, classical assumptions, and multiple linear regression tests with the help of SPSS version 27. The results show that brand image has a positive and significant effect on purchase interest, where product quality perception, brand reputation, and consumer trust are the main factors, while influencer endorsement also has a significant effect through credibility, relevance, and communication appeal. Simultaneously, these two variables explain 65.4% of the variation in consumer purchase interest, confirming that a marketing strategy combining a strong brand image and credible influencers can increase loyalty and purchasing decisions.